Unveiling the Evolutionary History of European Vipers and Their Venoms From a Multi‐Omic Approach - Adrián Talavera; Marc Palmada‐Flores; Fernando Martínez‐Freiría; Gabriel Mochales‐Riaño; Bernat Burriel‐Carranza; Maria Estarellas; Daniel Fernández‐Guiberteau; Álvaro Camina; Sylvain Ursenbacher; Judit Vörös; Bálint Halpern; Davinia Pla; et al. (Molecular Ecology, 2025)
Snake genomes attract significant attention from multiple disciplines, including medicine, drug bioprospection, and evolutionary biology. However, genomic research within the Viperidae family has mostly focused on the subfamily Crotalinae, while the true vipers (Viperinae) have largely been overlooked. European vipers ( Vipera ) have been the subject of extensive research due to their phylogeographic and ecological diversification, as well as their venoms. Nevertheless, phylogeography and systematics in this genus have primarily relied on biased information from mitochondrial genes, which fail to capture the likely effects of introgression and are prone to biases. On the other hand, venom research in this group has been conducted predominantly through proteomics alone. In this study, we generated chromosome‐level genome assemblies for three Vipera species and whole‐genome sequencing data for 94 samples representing 15 Vipera lineages. This comprehensive dataset allowed us to disentangle the phylogenomic relationships of this genus, affected by mito‐nuclear discordance and pervaded by ancestral introgression. Population‐level analyses in the Iberian Peninsula, where the three oldest lineages within Vipera meet, revealed signals of recent adaptive introgression between old‐diverged and ecologically dissimilar species, whereas chromosomal rearrangements isolate species occupying similar niches. Finally, using transcriptomic and proteomic data, we characterised the Vipera toxin‐encoding genes, in which opposing selective forces were unveiled as common drivers of the evolution of venom as an integrated phenotype.

Alongshore runup variability across contrasting beach states: Insights from field observations - Ashley David Gracia-Barrera; Amaia Ruiz de Alegría-Arzaburu; Giovanni Coco; Gonzalo Simarro; Daniel Calvete (Geomorphology, 2025)

Sediment leakage on the beach and upper shoreface due to extreme storms - Jorge Guillén; Gonzalo Simarro; Daniel Calvete; Francesca Ribas; Angels Fernández-Mora; Alejandro Orfila; Albert Falqués; Rinse de Swart; Amanda Sancho-García; Ruth Durán (Marine Geology, 2024)

A new instability mechanism related to high-angle waves - Albert Falqués; Nabil Kakeh; Daniel Calvete (Ocean Dynamics, 2018)

Effect of wave–bedform feedbacks on the formation of, and grain sorting over shoreface-connected sand ridges - Nicolette C. Vis-Star; Huib E. de Swart; Daniel Calvete (Ocean Dynamics, 2009)

Non-linear response of shoreface-connected sand ridges to interventions - Huib E. de Swart; Daniel Calvete (Ocean Dynamics, 2003)